The Effect of Al2O3 Additives on Some Mechanical Properties of Un Saturated Polyester Resin - Leabi, Suad Hamed (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This study included preparation for the unsaturated polyester samples before and after reinforced by the Alumina oxide powder of different volume fraction amounting (2%,4%,6%).    And this research included the study of some of mechanical properties such as (Hardness,compressive,wear).     The results showed that the increase of the hardness and compressive strength after the reinforced and the increase with the volume fraction increase.   As the wear test shows that the wear rate increases with applied load increase(5,10,15) from  (10.6-18.6) gm/cm befor reninforced and from(5.4-15.2)gm/cm,(4.7-12.9)gm/cm,(48.1)gm/cm,after reinforced from the different volume fraction, and the wear rate decrease with the volume fraction increase